Unique chemistry associated with diversification in a tightly coupled cycad-thrips obligate pollination mutualism. (June 2021) - Terry, L. Irene; Moore, Chris J.; Roemer, Robert B.; Brookes, Dean R.; Walter, Gimme H.
Abstract: Cycad cone thermogenesis and its associated volatiles are intimately involved in mediating the behavior of their obligate specialist pollinators. In eastern Australia, thrips in the Cycadothrips chadwicki species complex are the sole pollinators of many Macrozamia cycads. Further, they feed and reproduce entirely in the pollen cones. M. miquelii, found only in the northern range of this genus, is pollinated only by a C. chadwicki cryptic species that is the most distantly related to others in the complex. We examined the volatile profile from M. miquelii pollen and ovulate (receptive and non-receptive) cones to determine how this mediates pollination mechanistically, using GC-MS (gas chromatography-mass spectrometry) and behavioral tests. Monoterpenes comprise the bulk of M. miquelii volatile emissions, as in other Macrozamia species, but we also identified compounds not reported previously in any cycad, including three aliphatic esters (prenyl acetate and two of uncertain identity) and two aliphatic alcohols. The two unknown esters were confirmed as prenyl (3-methylbut-2-enyl) esters of butyric and crotonic ((E))-but-2-enoic) acids after chemical synthesis. Prenyl crotonate is a major component in emissions from pollen and receptive ovulate cones, is essentially absent from non-receptive cones, and has not been reported from any other natural source. In field bioassays, Cycadothrips were attracted only to those volatile treatments containing prenyl crotonate. We discuss M. miquelii cone odorants relative to those of other cycads, especially with respect to prenyl crotonate being a species-specific signal to this northern C. chadwicki cryptic species, and how this system may have diversified. Graphical abstract: Image 1 Highlights: Cones of Macrozamia miquelii, an Australian endemic, emit novel cycad volatiles. Two are hemiterpenes, commonly found in other plants. Three are prenyl esters: acetate, butyrate and crotonate. Prenyl crotonate, a major component, is not known from any other natural source. Prenyl crotonate attracts the species-specific thrips pollinator of M. miquelii.